Identification of an (−)‐englerin A analogue, which antagonizes (−)‐englerin A at TRPC1/4/5 channels. (25th January 2018) - Rubaiy, Hussein N; Seitz, Tobias; Hahn, Sven; Choidas, Axel; Habenberger, Peter; Klebl, Bert; Dinkel, Klaus; Nussbaumer, Peter; Waldmann, Herbert; Christmann, Mathias; Beech, David J
Abstract : Background and Purpose: (−)‐Englerin A (EA) is a potent cytotoxic agent against renal carcinoma cells. It achieves its effects by activation of transient receptor potential canonical (TRPC)4/TRPC1 heteromeric channels. It is also an agonist at channels formed by the related protein, TRPC5. Here, we sought an EA analogue, which might enable a better understanding of these effects of EA. Experimental Approach: An EA analogue, A54, was synthesized by chemical elaboration of EA. The effects of EA and A54 on the activity of human TRPC4 or TRPC5 channels overexpressed on A498 and HEK 293 cells were investigated, firstly, by measuring intracellular Ca 2+ and, secondly, current using whole‐cell patch clamp recordings. Key Results: A54 had weak or no agonist activity at endogenous TRPC4/TRPC1 channels in A498 cells or TRPC4 or TRPC5 homomeric channels overexpressed in HEK 293 cells. A54 strongly inhibited EA‐mediated activation of TRPC4/TRPC1 or TRPC5 and weakly inhibited activation of TRPC4. Studies of TRPC5 showed that A54 shifted the EA concentration–response curve to the right without changing its slope, consistent with competitive antagonism. In contrast, Gd 3+ ‐activated TRPC5 or sphingosine‐1‐phosphate‐activated TRPC4 channels were not inhibited but potentiated by A54. A54 did not activate TRPC3 channels or affect the activation of these channels by the agonist 1‐oleoyl‐2‐acetyl‐ sn ‐glycerol. Conclusions and Implications: This study has revealed a new tool compound for EA and TRPC1/4/5 channel research, which could be useful for characterizing endogenous TRPC1/4/5 channels and understanding EA‐binding sites and their physiological relevance.